Estilos de aprendizaje en estudiantes de quinto grado de secundaria en una institución educativa en la Región Callao - Matienzo Saivay, Celia Saturnina (2010)
This research was to determine whether there were significant differences in the learning styles of students from 5th grade secondary school according to gender. The sample was made up by 200 students from an educational institution in the Callao region. The survey instrument was questionnaire Honey-Alonso learning styles (2007). Findings allowed concluding that there are significant differences in the active level according to gender, being the score average, higher in the female to male. On the styles thoughtful, theoretical and pragmatic; no significant differences were found.